Rearrange x - y = 1 to form y = mx + b
Answers
Answered by
1
Answer:
y=x-1
Step-by-step explanation:
y = mx + b
given x - y = 1
x-1=y
y=x-1
where m=1,b=-1
Hope it helps
please mark it as brainliest.
Answered by
2
Answer:
y = x-1
Step-by-step explanation:
Here
m= 1
b=1
Procedure is that you have to shift the variable y on one side and all other terms other side .
Similar questions
Math,
5 months ago
Physics,
5 months ago
English,
5 months ago
Computer Science,
11 months ago
English,
11 months ago
Computer Science,
1 year ago